2014
DOI: 10.1126/scitranslmed.3008825
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Broad-Spectrum T Cells as Treatment for AdV, EBV, CMV, BKV, and HHV6 Infections after HSCT

Abstract: It remains difficult to treat the multiplicity of distinct viral infections that afflict immunocompromised patients. Adoptive transfer of virus-specific T-cells (VSTs) can be safe and effective, but such cells have been complex to prepare and limited in anti-viral range. We now demonstrate the feasibility and clinical utility of rapidly-generated single-culture VSTs that recognize 12 immunogenic antigens from 5 viruses (Epstein-Barr virus, adenovirus, cytomegalovirus, BK virus, and Human Herpesvirus 6) that fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
295
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 353 publications
(303 citation statements)
references
References 60 publications
4
295
0
4
Order By: Relevance
“…[85][86][87] Adoptive transfer of anti-HHV-6 T cells may effectively reduce the clinical manifestations of HHV-6 encephalitis or prevent HHV-6 diseases in the future.…”
Section: Hhv-6 Encephalitis After Allo-hct M Ogata Et Almentioning
confidence: 99%
“…[85][86][87] Adoptive transfer of anti-HHV-6 T cells may effectively reduce the clinical manifestations of HHV-6 encephalitis or prevent HHV-6 diseases in the future.…”
Section: Hhv-6 Encephalitis After Allo-hct M Ogata Et Almentioning
confidence: 99%
“…These studies have shown that even peripheral blood mononuclear cells (PBMCs) could be pulsed with peptides in the presence of cytokines to rapidly expand EB-VSTs, eliminating the need to make DCs. The cells manufactured using these accelerated and simplified strategies appear to be clinically effective [59], and the substantial reduction in time, complexity and cost has enabled the study of this approach in multi-national trials in lymphoma and NPC [55].…”
Section: Treatment Of Type 3 Latency Tumorsmentioning
confidence: 99%
“…These viruses are classified into highrisk and low-risk groups according to the propensity for malignant progression of the lesions that they cause. Persistent infection of high-risk subtypes, such as HPV- 16,18,31,33,35,39,45,51,52,56,58,59, or 66, has long been known to predispose to the development of cervical cancer [108] and is also associated with carcinomas of the oropharynx and anogenital region. HPV infects basal epithelial cells where viral genomes are persistently maintained as low-copy number episomes [4].…”
Section: Epidemiology and Pathogenesismentioning
confidence: 99%
“…With the availability of overlapping peptide libraries spanning individual EBV antigens, several groups have shortened the process and shown that rapidly expanded EBV-specific T-cells induce similar response rates. (Papadopoulou et al 2014a) (Icheva et al 2013) An alternative strategy to obtain rapidly available EBV-specific T-cells is to use banked “third-party” products derived from healthy donors. This approach has been tested in the clinic in patients with EBV-associated post transplant lymphoma with response rates of 60–80%.…”
Section: Targeting Tumour-associated Antigens With Native T-cell Recementioning
confidence: 99%
“…The infusions were well tolerated and, on further analysis, a distinguishing characteristic between responders and non-responders was the induction of post-infusion epitope spreading to the non-viral lymphoma antigens MAGEA4, Survivin, and PRAME. (Bollard et al 2014) The success of autologous EBV-CTL therapy prompted several groups to explore more rapid generation methods(Ngo et al 2014, Papadopoulou et al 2014a), as well as “off-the-shelf” strategies using healthy donor-derived T-cells for EBV+ lymphomas. (Vickers et al 2014)…”
Section: Targeting Tumour-associated Antigens With Native T-cell Recementioning
confidence: 99%